Epifaunal communities across marine landscapes of the deep Chukchi Borderland (Pacific Arctic). (September 2019) - Zhulay, Irina; Iken, Katrin; Renaud, Paul E.; Bluhm, Bodil A.
Abstract: Epifaunal communities from the poorly studied Arctic deep sea of the Chukchi Borderland region were investigated to: (1) determine differences in community structure among ridges, plateau with pockmarks, and much deeper basins as three main habitat types, (2) analyse the environmental factors that might shape these communities, and (3) investigate biogeographic affinities dominating the epifaunal communities. Epifaunal samples were collected in summer 2016 with a beam trawl (6 stations) and ROV (10 stations) from 486 to 2610 m depth. Seventy-eight and eighty-six taxa were registered from ROV images and trawl samples, respectively, with Echinodermata and Arthropoda dominating overall taxon richness. Epifaunal densities were estimated at 2273 to 14, 346 ind/1000 m 2 based on ROV images but only 342 to 2029 ind/1000 m 2 based on trawl samples. Epifaunal biomass based on trawl catches ranged from 173 to 906 g wet weight/1000 m 2 . There was no significant difference in density, biomass and community composition between plateau and ridge communities, though the western and eastern parts of the study area differed in plateau/ridge community properties. Abundance in the eastern part of the study area was dominated by annelids (Ampharetidae and Sabellidae), and the western part by an unknown cnidarian (likely polyps of Atolla ). Trawl samples from both western and eastern regions were dominated by the echinoderms Ophiopleura borealis and Pontaster tenuispinus . Deep basin communities differed from shallower plateau/ridge stations by significantly lower number of taxa and densities based on the images, and by lower biomass based on trawl catches. Polynoid annelids and sponges were characteristic taxa of the basin stations. Water depth and number of stones providing hard substrate significantly influenced epifaunal community structure, with sediment pigments and grain size also being influential. Arcto-boreal-Atlantic species dominated communities in the Chukchi Borderland, presumably mediated by Atlantic water dominance in the deep water layers of the Pacific Arctic. This study adds to the limited knowledge of ecology of the Arctic deep sea and improves existing baseline data that can be used to assess future effects of climate change on the system. Highlights: Deep Arctic Basin communities differed from those at shallower plateaus/ridges in composition, diversity, density and biomass. Regional (west/east) differences in numerically dominant taxa were found among plateau and ridge stations. Differences in communities were best explained by depth, presence stones, food availability, and sediment grain size. Arcto-boreal-Atlantic species dominated epifauna indicating a strong link with deep Atlantic water in the Chukchi Borderland.